The Transformation of Folklore into Digital Form: Innovation in Literature Learning in the Era of Generative AI - Iis Aprinawati; Nurmalina (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This study aims to describe the process and impact of transforming local folklore into digital formats using generative AI technology as an innovation in literature education at the Elementary School Teacher Education Program (PGSD), Universitas Pahlawan Tuanku Tambusai. This research uses a Research and Development (R&D) methodology with a mixed-methods approach, encompassing a needs survey, product development, and effectiveness testing among PGSD students. The developed digital product consists of folklore reimagined through generative AI (including text, voice narration, automatic illustration, and interactivity) to enhance literary appeal and comprehension. The results indicate that the transformation achieved high satisfaction and readability scores among students, while also improving motivation, literary appreciation, and digital literacy skills. The findings also reveal several technical and conceptual challenges, such as content originality, quality of voice and illustrations, and readiness of lecturers and infrastructure. In conclusion, utilizing generative AI to transform folklore into digital learning materials is an innovative, feasible, and effective strategy for enhancing literature learning in the PGSD program at Universitas Pahlawan Tuanku Tambusai.